ОСОБЛИВОСТІ ФОРМУВАННЯ УГРУПОВАНЬ МІКРООРГАНІЗМІВ ЧОРНОЗЕМУ ТИПОВОГО ПІД ЧАС ВИРОЩУВАННЯ СУНИЦІ САДОВОЇ ЗА РІЗНИХ СИСТЕМ УДОБРЕННЯ І КРАПЛИННОГО ЗРОШЕННЯ - Н. І. , Ковалжи (Institute of Agrocultural Microbiology and Agro-industrial Manufacture of NAAS of Ukraine, 2021)
Objective. To determine the influence of fertilization systems on the parameters of the number of separate ecological and trophic groups of microorganisms in typical deep heavy loam chernozem upon bed technology of garden strawberry cultivation with the use of drip irrigation. Methods. Comparative profile, microbiological, mathematical and statistical. Results. Seasonal changes in the number of microorganisms depend on many factors, including physical, chemical, biological, environmental. Conducted studies show that most factors tend to increase the number of microorganisms in the soil in spring and summer and decrease to a minimum in autumn. With depth, the number of microorganisms decreases. The highest number of them was detected in the ridge part of the soil. Soil biogenicity varied from 8.75 million CFU /1 g of dry soil in the grassland soil up to 5.67 million CFU/1 g of dry soil upon growing strawberries without fertilizers in a 0–10-centimetre layer of soil; the use of organic and mineral fertilizers had an equally positive effect on biogenicity. Conclusion. The terms of sampling have a significant impact on the number of representatives of different ecological and trophic groups of microorganisms of typical deep heavy loam chernozem. Cultivation, fertilization and irrigation of soil affect the development of micromycetes, amylolytics, ammonifiers, oligonitrophils and oligocarbophils. According to a study, cultivation of garden strawberry requires constant application of fertilizers to eliminate imbalances of nutrients, including organic matter, as evidenced by high oligotrophic coefficient and low nitrogen mobilization rate.